Evaluasi Kinerja Alat Pemberi Isyarat Lalu Lintas (APILL) Menggunakan Metode Manual Kapasitas Jalan Indonesia 1997 Dan Webster - Marissa Octaviany Girsang; Rudatin Ruktiningsih (G-SMART, 2019)
The development of transportation occurs along with the development of residents in an area. The impact caused a buildup of vehicles on the highway. Transportation growth is linearly related to the Traffic Light Signaling Tool (APILL). Giving a Traffic Giver Tool is one way to regulate traffic. The methods that can be used for the duration of the APILL include the 1997 Indonesian Road Capacity Manual Method and Webster. The location of the study was in the Simpang Statue area of Pangeran Diponegoro and Abdulrahman Saleh. The webster method is calculated based on vehicles that come randomly. The calculation of the webster method is used to calculate the average delay of a vehicle when approaching an intersection where this delay occurs due to the large number of vehicles entering compared to the vehicle coming out of the intersection. the use of this webser method aims to be able to produce the optimum cycle time at each intersection. The Indonesian Road Capacity Manual Method (MKJI 1997) is a manual for road traffic calculations but cannot be used to analyze networks. This intersection obtains a degree of saturation average of ≥ 0.75, meaning that this intersection experiences a buildup of vehicles or congestion. The capacity and volume of vehicles in each intersection are inversely proportional. The intersection capacity can only accommodate around 2500 vehicles / hour but when on the field there are 7200 vehicles / hour. This makes APILL not work in each intersection. Simpang Statue of Pangeran Diponegoro and Abdulrahman Saleh is included in the F service (low speed blocked flow). The duration of the APILL time is not the same every day because the vehicle volume changes in each hour so that it is designed several plan APILL in the intersection. To overcome this kind of incident can be assisted by officers from the Police or the Semarang City Transportation Agency. Until now the APILL method still uses the Indonesian Road Capacity Manual 1997. Compared to the Webster method, the data needed is very minimal or incomplete. The results of the APILL time duration obtained using the 1997 Indonesia Jalan Capacity Manual method differ from the duration of time in the field and generally the results of calculations the duration of time obtained from this method added 10% of the calculation results and applied in the field.